2022
DOI: 10.1177/2333794x221078708
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Adverse Childhood Experiences on Health and Development in Young Children

Abstract: In recent years, there have been advances in research regarding the prevalence of Adverse Childhood Experiences (ACEs) and resulting poor outcomes for children who have experiences ACES. ACE exposure has been connected with poor academic performance, poor health outcomes, and certain diseases. However, there is still relatively little known about the prevalence and impact of ACE exposure in early childhood. Using the 2016 National Survey of Children’s Health, this study assessed the prevalence of adverse child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 19 publications
0
28
0
2
Order By: Relevance
“…52 Early identification of these mechanisms as well as substance use initiation patterns can help develop early interventions, access to mental health services, supportive relationships, and resiliencebuilding strategies for children to cope with their experiences. [53][54][55][56][57] Finally, this study demonstrated that LCA is useful in identifying subgroups with shared risk factors that can benefit from a common intervention. 21 First, in consideration of ACE-related items, LCA can use maximum likelihood estimation to form internally homogenous and externally heterogeneous subgroups to investigate their shared risk and protective factors.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…52 Early identification of these mechanisms as well as substance use initiation patterns can help develop early interventions, access to mental health services, supportive relationships, and resiliencebuilding strategies for children to cope with their experiences. [53][54][55][56][57] Finally, this study demonstrated that LCA is useful in identifying subgroups with shared risk factors that can benefit from a common intervention. 21 First, in consideration of ACE-related items, LCA can use maximum likelihood estimation to form internally homogenous and externally heterogeneous subgroups to investigate their shared risk and protective factors.…”
Section: Discussionmentioning
confidence: 68%
“…Finally, substance use can perpetuate a cycle of adverse experiences, as it can lead to criminal behaviors, legal problems, and further adverse events, creating a negative feedback loop 52 . Early identification of these mechanisms as well as substance use initiation patterns can help develop early interventions, access to mental health services, supportive relationships, and resilience‐building strategies for children to cope with their experiences 53‐57 …”
Section: Discussionmentioning
confidence: 99%
“…Adverse childhood experiences (ACEs) include traumatic and life-stressor events of a heterogenous nature, associated with lower psychological resilience at a young age [ 119 ], health risk behaviors and poor health in later life [ 120 , 121 , 122 , 123 , 124 ], immune dysregulation and immune system inflammation [ 124 , 125 , 126 ], as well as with a negative impact on the long-term developmental trajectory [ 123 , 127 ]. Inevitably, the diagnoses of both SLE and AN has also been researched in the context of ACEs.…”
Section: Discussionmentioning
confidence: 99%
“…Children exposed to ACEs are at increased risk of developing behavioral challenges, both in and out of the school environment. Such challenges include difficulties with interpersonal relationships, self‐regulation, social competence, and academic development (Thurston et al, 2018; Webster, 2022), as well as poorer academic outcomes and greater risk for developing mental health difficulties such as depression and anxiety (Perfect et al, 2016). These behaviors are problematic in the school environment, as educators and other school staff are tasked with effectively managing these behaviors.…”
Section: Introductionmentioning
confidence: 99%